Visualisierungen von Kult - Meyer, Marion (2014)
"Visualizations of cult" deals with the strategies of visual representations of cult as well as with concretisations of its visualization, in the perspective of historical and cultural studies. Cult is understood in a broad sense, describing modes of collective veneration and auratization, in religious, quasi-religious or trivial-profane connections. Cult practice and experience and their manifestations are treated under five aspects: (1) objects: staging of cult, (2) subjects: experiences of cult, (3) cult of persons, (4) spaces of cult, (5) manifestations of cult practice.